2020
DOI: 10.1242/dev.186874
|View full text |Cite
|
Sign up to set email alerts
|

ALTERED MERISTEM PROGRAM1 regulates leaf identity independently of miR156-mediated translational repression

Abstract: In Arabidopsis, loss of the carboxypeptidase ALTERED MERISTEM PROGRAM1 (AMP1) produces an increase in the rate of leaf initiation, an enlarged shoot apical meristem and an increase in the number of juvenile leaves. This phenotype is also observed in plants with reduced levels of miR156-targeted SQUAMOSA PROMOTER BINDING PROTEIN-LIKE (SPL) transcription factors, suggesting that AMP1 might promote SPL activity. However, we found that the amp1 mutant phenotype is only partially corrected by elevated SPL gene expr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 37 publications
(48 reference statements)
1
3
0
Order By: Relevance
“…One possible explanation for this discrepancy might be that release of translational repression of miRNA targets is restricted to the AMP1/LAMP1 expression domain and/or affects only a subset of miRNA targets with a role in embryo and SAM patterning. The latter is supported by a recent study, in which no translational de-repression of miR156 target SPL9 or the miR159 target MYB33 could be observed in amp1 [41]. We showed that AMP1 acts through the AP2 transcription factor RAP2.6L, which is controlled by the miRNA-regulated HD-ZIP III proteins [22] and we are currently analyzing the functional relationship between HD-ZIP III mis-regulation and amp1 phenotypes.…”
Section: Plos Geneticssupporting
confidence: 75%
“…One possible explanation for this discrepancy might be that release of translational repression of miRNA targets is restricted to the AMP1/LAMP1 expression domain and/or affects only a subset of miRNA targets with a role in embryo and SAM patterning. The latter is supported by a recent study, in which no translational de-repression of miR156 target SPL9 or the miR159 target MYB33 could be observed in amp1 [41]. We showed that AMP1 acts through the AP2 transcription factor RAP2.6L, which is controlled by the miRNA-regulated HD-ZIP III proteins [22] and we are currently analyzing the functional relationship between HD-ZIP III mis-regulation and amp1 phenotypes.…”
Section: Plos Geneticssupporting
confidence: 75%
“…In Arabidopsis, miR156/157 regulate the expression of 10 SPL genes 51,83,92 through a combination of transcript cleavage 94,95 and translational repression 96,97 , with translational repression being the dominant mechanism 52 . A recent genetic analysis suggests the cellular site of translational repression by miR156 may differ from that of other miRNAs 98 . Some of the effects of the miR156/SPL module are mediated by miR172.…”
Section: Regulation Of Vegetative Phase Change By the Mir156/spl Modulementioning
confidence: 99%
“…Interestingly, it is generally believed that miRNA-mediated translational repression requires AMP1 gene, while siRNA-mediated translational repression does not require AMP1 gene ( Wu et al, 2020 ; Yang et al, 2021a ). However, recent studies have shown that AMP1 does not prevent translational repression of the SPL9 gene (target of miR156) or MYB33 gene (target of miR159), suggesting that AMP1 is not universally required for miRNA-mediated translational repression ( Fouracre et al, 2020 ). In addition, sRNAs play an important role in the regulation of diverse plant phytohormones by controlling key factors involved in translational repression ( Li et al, 2020 ).…”
Section: Srna Functionsmentioning
confidence: 99%